Operationalizing the blue economy in the Gulf of Guinea, Africa - Popoola, Olusola Olalekan; Olajuyigbe, Ayo Emmanuel (Frontiers in Political Science, 2023)
The Blue Economy is crucial for sustainable development in Africa, and the Gulf of Guinea, one of Sub-Saharan Africa's most economically dynamic countries, faces several challenges in transitioning into this economy. This study assesses the situation of the Blue Economy in the Gulf of Guinea and proposes strategies for its operationalization. A qualitative research approach was used to examine each member state's marine conservation initiatives, regional collaboration, management approaches, and strategic frameworks. Findings show that the Gulf of Guinea is already experiencing blue economy activities, but challenges like rapid population growth, urbanization, piracy, unsustainable anthropogenic activities, poor institutional frameworks, and climate change hinder the transition. The Gulf of Guinea's ocean economy accounts for less than 10% of GDP, so integrating the blue economy into trade strategies is crucial for its transformation. A systematic approach based on national priorities, social context, and resource base is needed to foster social inclusion, economic progress, and sustainable ocean development. Enablers of blue growth, such as integrated coastal zone management, marine spatial planning, marine protected areas, marine biodiversity, and blue justice discourse, must be integrated into policy design, prioritizing sustainability and equity. A cautious, phased approach is suggested, focusing on establishing traditional sectors, growing them, integrating value chains, and implementing regional collaboration so that the blue economy delivers on its social, environmental and economic goals in the Gulf of Guinea.